GOVERNMENT AND COMMUNITY EFFORTS IN FLOOD DISASTER RISK MANAGEMENT CASE STUDY: TOAHA VILLAGE - PAKUE DISTRICT - KOLAKA UTARA - SOUTHEAST SULAWESI - INDONESIA - sudarwin kamur; Risaldi Risaldi; Nasarudin Nasarudin (Geographica: Science and Education Journal, 2022)
This reseach is motivated because the flood disaster that occurred in Toaha village was caused by having a lowland area, overflowing river water exceeding the capacity of the river, low topography, the effect of the collapse of the embankment and the amount of sediment in the sewer. This study discusses the efforts of the government and the community in managing flood risk in Toaha Village, Pakue District, North kolaka Regency seen from 1) Efforts, 2) Impact, 3) Cooperation Relationships, 4) Government Policies, the purpose of this research in general is to get an overview of the efforts of the government and the community of Toaha Village, Pakue District, Nort Kolaka Regency. This type of research is qualitative. The type of sampling used is purposive, assign informants based on research criteria. Collecting data carried out interview techniques. Based on data analysis using analysis that makes an explanation that can later provide a concrete explanation. From the result of this study indicate that the efforts made by the Toaha village community before the flood occurred were to be alert and careful when the rainy season arrived, when the flood came, people ran to a high and safe place, after the flood the people returned home, the second effort made by the government before the flood occurred was to urge the public to be careful during the rainy season, when the flood came, the local government contacted the sub-district head and the central government to the community, when the plood recedes, the government directs its people to return home and clean up the garbage that enters the house, the three impeacth that often occur after a flood are that people cannot carry out their usual activities  because people are busy cleaning their homes, children cannot go to school. Fourth, the relationship between the community and the government is good, the government has facilitated in terms of flood disaster management. Government policy.